Mochlos IB : period III, neopalatial settlement on the coast, the artisans' quarter, and the farmhouse at Chalinomouri, the neopalatial pottery - Barnard, Kellee A., 1968- (Prehistory monographs, 2003)
Mochlos is a Minoan town set on a fine harbour at the eastern side of the Gulf of Mirabello, in northeast Crete. It was first inhabited during the Neolithic period, and it had an important Minoan settlement during most of the Bronze Age. Mochlos I, to be published in three volumes, presents the results of the excavations in the Neopalatial levels of the Artisans' Quarter, and at the farmhouse at Chalinomouri. The Artisans' Quarter consisted of a series of workshops with evidence for pottery manufacture, metalworking, and weaving. Chalinomouri, a semi-independent farmhouse with strong connecti.